Examination management system (EXAMS) / Muhammad Fahmi Mohd Adzmi ... [et al.] - Mohd Adzmi, Muhammad Fahmi; Che Husin, Muhamad Badrul Amin; Abd Halim, Siti Nor Arifah; Arshad, Izzatil Husna; Mohamad Rosman, Mohamad Rahimi (Universiti Teknologi MARA, Kedah, 2019)
The Examination Management System (EXAMS) is a system created with the objectives to assist various types of users to manage and monitor the examination activities. Initially, it was reported that invigilators find difficulties in checking examination schedule as there was limited online platform, as well as attendance of invigilators and students are recorded manually by filling paper-based forms. Therefore, users (invigilators and students) can benefited from the system by being able to monitor the examination schedule through online platform anywhere. The attendance of invigilators and students are also recorded for each examination session. Furthermore, invigilators can generate reports for any issues during the examination. Next, invigilators can use this system to manage their duties such as exchanging duties, if needed. This system could also impact to promote part-time job opportunities, whereby the external users (not the staff or students of the universities / colleges) to apply as assistant exam invigilators. Thus, this system is relevant to any educational institutions that practice examinations as part of their teaching and learning activities to measure students’ performance. Examinations activities eventually can be managed at ease and evidence of each examination session are kept digitally. This will ensure users’ satisfactions by having productive works which equipped with user friendly interface.